2023
DOI: 10.1097/ico.0000000000003294
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 110- and 145-µm Small-Incision Lenticule Extraction Cap Thickness: A Randomized Contralateral Eye Study

Abstract: Purpose: To investigate the visual, refractive, and biomechanical outcomes of small incision lenticule extraction (SMILE) with two different cap thicknesses.Methods: Thirty-four patients were included in this prospective, randomized, contralateral eye study. Subjects were randomized to receive SMILE surgery with a 110-m cap thickness in one eye and 145-mm cap thickness in the fellow eye. Uncorrected and corrected distance visual acuity, contrast sensitivity (CS), total higherorder aberrations (THOAs) and corne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…This finding is consistent with the corneal biomechanical characteristics anatomically and theoretically. The anterior stroma contributes more to the biomechanical stability of the cornea than the posterior stroma, and a thicker corneal cap could spare more anterior stroma and minimize changes in the biomechanics after SMILE [ 9 , 33 ] although Liang [ 34 ] concluded that there was no significant difference in biomechanics among corneal caps with different thicknesses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with the corneal biomechanical characteristics anatomically and theoretically. The anterior stroma contributes more to the biomechanical stability of the cornea than the posterior stroma, and a thicker corneal cap could spare more anterior stroma and minimize changes in the biomechanics after SMILE [ 9 , 33 ] although Liang [ 34 ] concluded that there was no significant difference in biomechanics among corneal caps with different thicknesses.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, for some patients with thin corneas, the surgeon may choose a thinner cap thickness design rather than a randomized cap thickness in clinical practice. Some contralateral eye studies that adopted a randomized study design pertaining to cap thickness demonstrated that mean CCT should be more than 550 μm preoperatively to ensure the safety of the surgery [ 9 , 11 , 33 ]. Second, it would be a better statistical design that data collected and analyzed from one eye per patient.…”
Section: Discussionmentioning
confidence: 99%